2018
DOI: 10.1016/j.csi.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Revising IEC 80001-1: Risk management of health information technology systems

Abstract: IEC 80001-1 was published in 2010 and is now undergoing revision. Feedback gathered on the adoption of the standard has revealed a number of barriers that have impacted its adoption. The standard provides requirements related to the roles, responsibilities and activities that need to be performed for the risk management of medical IT networks. One reported barrier is a lack of drivers to motivate Top Management to implement the standard. In addition, there is a lack of alignment between IT and biomedical engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…A PRM and a PAM have been developed enabling risk management improvement. Healthcare Delivery Organizations can assess risk management process capability considering the requirements of IEC 80000‐1 which is the application of risk management to IT‐networks . This risk management life cycle process model provides specific risk management processes in the medical sector.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A PRM and a PAM have been developed enabling risk management improvement. Healthcare Delivery Organizations can assess risk management process capability considering the requirements of IEC 80000‐1 which is the application of risk management to IT‐networks . This risk management life cycle process model provides specific risk management processes in the medical sector.…”
Section: Related Workmentioning
confidence: 99%
“…Healthcare Delivery Organizations can assess risk management process capability considering the requirements of IEC 80000-1 which is the application of risk management to IT-networks. 43 This risk management life cycle process model provides specific risk management processes in the medical sector. After some feedback on the barriers preventing the adoption of the standard, a new approach for simplifying the standard usage has been proposed for its revision.…”
Section: Developed the Prorisk Managementmentioning
confidence: 99%
“…Lack of trained staff, responsibilities, budget, and management support Literature [25][26][27][28][29][30][31][32][33][34] The existing standards are too complex and complicated to implement Literature [27,30,[35][36][37] Limited knowledge about market-specific regulatory requirements, security standards, and policies…”
Section: Challenges Sourcesmentioning
confidence: 99%
“…It is also reported that BMEs do not understand complex networking concepts. They "do not speak the same language" [12]. [13].…”
Section: B Implementation and Adoption Challengesmentioning
confidence: 99%